Density-dependent competition and selection on immune function in genetic lizard morphs - Svensson, Erik (The National Academy of Sciences, 2001)
Density-dependent territorial interactions have been suggested to cause immunosuppression and thereby decrease fitness, but empirical support from natural populations is lacking. Data from a natural lizard population (Uta stansburiana) showed that breeding females surrounded by many territorial neighbors had suppressed immune function. Furthermore, variation in immunological condition had different effects on the fitness of the two heritable female throat-color morphs in this population. These interactive fitness effects caused correlational selection between female throat color and immune responsiveness. Population genetic theory predicts that this should have lead to the buildup and preservation of a genetic correlation between female morphotype and immunological condition. Accordingly, the throat color of a female was genetically correlated (r(A) = −1.36; SE = 0.55) with her daughter's immune responsiveness.